ANALISIS TINGKAT PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN PANDEGLANG - Ratu Dewi Nurmayangsari; Shalma Nur Fadilla; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Community welfare is an indicator of developme t goals. In its implementation, economic development will be faced with various problems that can hinder the success of such development. One of the complex problems related to the prosperity of the population is poverty. High poverty can have an impact on the emergence of various other social problems. It is difficult to know the exact cause and how effective control is to reduce poverty in Pandeglang Regency. The use of analytical tools in this study was carried out to identify and determine specific problems as a factor in the occurrence of poverty in Pandeglang Regency. In addition, this analysis method will contain information about events that must be considered in the scope of poverty alleviation that occurred in Pandeglang district. The final part of this journal discusses the design of poverty control procedures in Pandeglang Regency in approximately five years. Finally, it is hoped that the final results of this research will be very important to prevent poverty in Pandeglang Regency.